2021
DOI: 10.3389/fphar.2020.585740
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Attenuates the Contribution of Endogenous Nitric Oxide but Not Nitroxyl to Endothelium Dependent Relaxation of Rat Carotid Arteries

Abstract: Conclusion:Both NO• and HNO contribute to endothelium-dependent relaxation in carotid arteries. In diabetes, NO•-mediated relaxation is impaired, whereas HNO-mediated relaxation was preserved. The potential for preserved HNO activity under pathological conditions that are associated with oxidative stress indicates that HNO donors may represent a viable therapeutic approach to the treatment of vascular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 113 publications
(165 reference statements)
0
6
0
Order By: Relevance
“…The level of non–endothelium‐dependent vasodilation was detected by using intraperitoneal injection of sodium nitroprusside (SNP; 0.05 mg/kg), and the level of endothelium‐dependent vasodilation was detected separately by using intraperitoneal injection of acetylcholine (Ach; 0.05 mg/kg) or INS (1 U/kg) [17–19]. Intraperitoneal injection of an equal amount of saline was performed as the vehicle Ctrl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of non–endothelium‐dependent vasodilation was detected by using intraperitoneal injection of sodium nitroprusside (SNP; 0.05 mg/kg), and the level of endothelium‐dependent vasodilation was detected separately by using intraperitoneal injection of acetylcholine (Ach; 0.05 mg/kg) or INS (1 U/kg) [17–19]. Intraperitoneal injection of an equal amount of saline was performed as the vehicle Ctrl.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, our study is the first to uncover the harmful effect of ASP on the vascular endothelium and its involvement in lipid metabolism in obesity, which may point out a new direction for ASP as a therapeutic target for vascular diseases. 0.05 mg/kg), and the level of endothelium-dependent vasodilation was detected separately by using intraperitoneal injection of acetylcholine (Ach; 0.05 mg/kg) or INS (1 U/kg) [17][18][19]. Intraperitoneal injection of an equal amount of saline was performed as the vehicle Ctrl.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…One of the biggest groups of naturally occurring polyphenolic substances, flavonoids, are well-recognised to possess several biological activities, including antioxidant, anti-inflammatory, and vasodilatory properties [ 7 , 8 , 9 ]. Given that oxidative stress and inflammation are common features reported in endothelial dysfunction, a critical and initiating factor for several vascular complications [ 10 , 11 , 12 , 13 ], flavonoids are widely considered as potential sources of natural product to exert beneficial effects on the cardiovascular system [ 14 ]. Indeed, several previous studies have shown that flavonoids present in orange peel waste (OPW) possessed antioxidant and anti-inflammatory properties [ 15 , 16 ] although less is known on the effects of OPW in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a diabetic rat model, injection of STZ increased ROS and caused endothelial cell dysfunction, which resulted in decreased formation of NO and cGMP in aortic tissue. Therefore, natural products that have antioxidant effects can be used to prevent endothelial cell damage in diabetes [ 17 , 18 , 19 ]. The antioxidants from natural products such as Cinnamomum cassia and Heterotrigona itama could be used as protection against endothelial cell dysfunction in diabetic complications, as they are shown to decrease ROS and increase the NOS, NO, and cGMP in rat aortic tissue that was given streptozotocin intraperitoneally [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%